Digital Tourism Business Ecosystem: Artifacts, Taxonomy and Implementation Aspects (International Journal of Innovative Research in Computer Science & Technology, 2021)
Digitalization and inter-connectedness of  business systems have increased the dependency between  business entities. The ever-changing environment and  business demands have increased competition and  collaboration among diverse entities, which have forced the  concept of ecosystem models. This work highlights the  need for a digital tourism business ecosystem model for the  tourism industry of Nepal. The work is built on interviews  with experts from the Nepal tourism sector and the study of  literature, reports, and publications in the field of tourism  and digitalization in tourism of Nepal. Interviews are  carried out on a one-to-one basis with 30 selected industry  experts as a source of information and data. The study  builds a taxonomy of different scenarios of tourism, a  conceptual model for the Digital Tourism Business  Ecosystem, and an Implementation model for Nepal.  Further, as the selection of resources is a crucial factor in  Digital Business Ecosystem, an Analytical hierarchical  processing model is proposed as a solution for resource  selection and optimization. This work is important as it  brings out the need for a Digital Tourism Business  Ecosystem in today's context, especially for the tourism  industry. Secondly, it demonstrates the practical aspects of  the Digital Tourism Business Ecosystem Model for Nepal.  The work can further serve as a reference and knowledge  base for digital business system analysts, system designers, and digital tourism business implementers for better digital  business system designs and implementation in the tourism  sector.
Keywords: Digitalization; digital ecosystem; digital species; integrated systems; taxonomy; Nepal tourism